2019
DOI: 10.1158/0008-5472.can-18-0881
|View full text |Cite
|
Sign up to set email alerts
|

Targeting APLN/APLNR Improves Antiangiogenic Efficiency and Blunts Proinvasive Side Effects of VEGFA/VEGFR2 Blockade in Glioblastoma

Abstract: Antiangiogenic therapy of glioblastoma (GBM) with bevacizumab, a VEGFA-blocking antibody, may accelerate tumor cell invasion and induce alternative angiogenic pathways. Here we investigate the roles of the proangiogenic apelin receptor APLNR and its cognate ligand apelin in VEGFA/VEGFR2 antiangiogenic therapy against distinct subtypes of GBM. In proneural GBM, apelin levels were downregulated by VEGFA or VEGFR2 blockade. A central role for apelin/APLNR in controlling GBM vascularization was corroborated in a s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 56 publications
3
75
0
Order By: Relevance
“…The effects of Apelin depletion on tumor cells and the cells of the tumor microenvironment might be model and context dependent. A recent publication found that Apelin depletion presents a double‐edged sword in glioblastoma, since it enhanced tumor cell invasion, while at the same time reducing vascular density, without accompanied changes in immune cell infiltration (Mastrella et al , ). In contrast to this study in glioblastoma, we find a consistent benefit of depleting Apelin in epithelial breast and lung cancer, associated with normalized vessel function, decreased hypoxia, and consequently reduced metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of Apelin depletion on tumor cells and the cells of the tumor microenvironment might be model and context dependent. A recent publication found that Apelin depletion presents a double‐edged sword in glioblastoma, since it enhanced tumor cell invasion, while at the same time reducing vascular density, without accompanied changes in immune cell infiltration (Mastrella et al , ). In contrast to this study in glioblastoma, we find a consistent benefit of depleting Apelin in epithelial breast and lung cancer, associated with normalized vessel function, decreased hypoxia, and consequently reduced metastases.…”
Section: Discussionmentioning
confidence: 99%
“…In the tumor, border dispersed cells strongly positive for TSPO were visible (Figure 2A, arrows in the tumor border), likely showing invading cells and macrophages, while in the tumor-free regions, these expression patterns were weaker ( Figure 2A, arrows in tumor-free areas). Next, we used a panel of genetically engineered mouse GBM cells that faithfully recapitulate the key pathological features for each GBM subtype (Table A1) [24]. By immunofluorescent staining against TSPO, the distinction between tumor-free brain and tumor samples became obvious when using murine Gl261, as well as the classical cdkn2a KO EGFRvIII or proneural 53 KO PDGFB GSCs ( Figure 2B).…”
Section: Tspo Expression Is Upregulated In Gbmmentioning
confidence: 99%
“…GBM stem-like cells (GSCs) were derived from human GBM of different genetic subtypes, namely proneural [20,21] and classical [22], and were cultured as spheroids until xenografting them into immunodeficient mouse brains to produce GBM. Mouse transgenic GSCs used to model genetic GBM subtypes were derived from transgenic neural precursor cells that were additionally transduced to carry typical driver mutations for proneural (p53 KO PDGFB) or classical (cdkn2a KO EGFRvIII) GBM subtypes [23,24] and were kept under stem cell-like conditions until orthotopic implantation into immunocompetent mice. By the immunostaining of GBM patient samples, patient-derived xenografts, and murine genetic subtype models, we show that TSPO expression is detected in tumor cells, as well as the tumor microenvironment, especially tumor-associated myeloid cells, pericytes, and endothelial cells, while LAT1 seems to be restricted to the tumor cells themselves.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of suppressing Apelin expression in cancer may however be dependent on the cancer type. In glioma, Apelin depletion resulted in increased tumor invasive behavior (Mastrella et al , ). However, in agreement with the results from the Uribesalgo study, suppression of Apelin function combined with anti‐angiogenic therapy resulted in efficient decrease in glioma progression (Mastrella et al , ).…”
Section: Unlike Vessels In the Healthy Tissue Tumor Vessels Are Abnomentioning
confidence: 99%
“…In glioma, Apelin depletion resulted in increased tumor invasive behavior (Mastrella et al , ). However, in agreement with the results from the Uribesalgo study, suppression of Apelin function combined with anti‐angiogenic therapy resulted in efficient decrease in glioma progression (Mastrella et al , ). On the other hand, studying the effect of overexpression of Apelin in murine colon26 adenocarcinoma and Lewis lung carcinoma, Kidoya et al showed impaired tumor growth and reduced tumor vessel permeability as a consequence of Apelin overexpression (Kidoya et al , ).…”
Section: Unlike Vessels In the Healthy Tissue Tumor Vessels Are Abnomentioning
confidence: 99%